2013
DOI: 10.1248/bpb.b13-00657
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Depression-Like Behavior and Memory Impairment with the Ethanol Extract of <i>Pleurotus eryngii</i> in Ovariectomized Rats

Abstract: Ethanol extract of Pleurotus eryngii (DC.) QUÉL has estrogen-like activities that protect against bone loss caused by estrogen deficiency. In the present study, we investigated the effect of P. eryngii on depression-like behavior and memory impairment in ovariectomized (OVX) rats. Immobility time during a forced swimming test was significantly longer for OVX rats than for sham-operated rats. The depression-like behavior in OVX rats was improved by long-term administration of the ethanol extract of P. eryngii (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…There are some researches related to estrogen-like drugs which improved neurological symptoms such as depression and memory impairment caused by surgical or natural menopause [36][37][38]. To determine whether the ethanol extracts of this Pleurotus eryngii (PEE) has estrogen-like activity, Minami et al [39] fed the extracts to the OVX rats and observed the immobility time of the OVX rats with the treatment of the extracts was significantly shortened during a forced swimming test. The Morris water maze test showed that spatial memory impairment in OVX rats was improved by PEE.…”
Section: Estrogen-like Activitymentioning
confidence: 99%
“…There are some researches related to estrogen-like drugs which improved neurological symptoms such as depression and memory impairment caused by surgical or natural menopause [36][37][38]. To determine whether the ethanol extracts of this Pleurotus eryngii (PEE) has estrogen-like activity, Minami et al [39] fed the extracts to the OVX rats and observed the immobility time of the OVX rats with the treatment of the extracts was significantly shortened during a forced swimming test. The Morris water maze test showed that spatial memory impairment in OVX rats was improved by PEE.…”
Section: Estrogen-like Activitymentioning
confidence: 99%
“…The species used in all of the animal models were limited to rats and mice: we did not find instances of other rodent species that have been utilized as antidepressant screens ( Kramer et al, 1998 ; Alo et al, 2019 ). Fourteen of the studies used rats ( Matsuzaki et al, 2013 ; Minami et al, 2013 ; Tan et al, 2016 ; Liu C. et al, 2017 ; Song et al, 2017 ; Wang et al, 2017 ; Huang et al, 2020 ; Nascimento et al, 2020 ; Lin et al, 2021a ; Zhang L. et al, 2021 ; Lin et al, 2021b ; Anuar et al, 2022 ; Cheng, 2023 ; Rakoczy et al, 2023 ), while the remaining 36 studies used mice to test for antidepressant-like effects ( Zhou et al, 2005 ; Nishizawa et al, 2007 ; Koo et al, 2008 ; Singh et al, 2014 ; Tianzhu et al, 2014 ; Socala et al, 2015 ; Yao et al, 2015 ; Gupta et al, 2016 ; Huang et al, 2016 ; Nakamichi et al, 2016 ; Song et al, 2016 ; Xu, 2016 ; Bao et al, 2017 ; Liu Y. et al, 2017 ; Lin et al, 2017 ; Chiu et al, 2018 ; Mahmoudi et al, 2018 ; Ryu et al, 2018 ; Jin et al, 2019 ; Li et al, 2019 ; Song et al, 2020 ; Li H. et al, 2021 ; Li TJ. et al, 2021 ; Zhang T. et al, 2021 ; Chong et al, 2021 ; Hossen et al, 2021 ; Park et al, 2021 ; Singh et al, 2021 ; Zhao et al, 2021 ; Chou et al, 2022 ; Mi et al, 2022 ; Xin et al, 2022 ; Yu et al, 2022 ; Ezurike et al, 2023 ; Zhao et al, 2023 ; Hernandez-Leon et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Morris water maze test was performed as previously described [20]. Briefly, a transparent platform (10 cm in diameter) was submerged in a pool (130 cm in diameter) filled with water (22°C ± 2°C) and surrounded by a grey wall (57 cm in height) and two different objects.…”
Section: Methodsmentioning
confidence: 99%